A biomarker‐based study of prenatal smoking exposure and autism in a Finnish national birth cohort. Issue 11 (10th September 2021) - Cheslack‐Postava, Keely; Sourander, Andre; Hinkka‐Yli‐Salomäki, Susanna; McKeague, Ian W.; Surcel, Heljä‐Marja; Brown, Alan S.
Abstract: Maternal exposure to tobacco smoke during pregnancy is a common and persistent exposure linked to adverse neurodevelopmental outcomes in the offspring. However, previous studies provide mixed evidence regarding the relationship between prenatal smoking and offspring autism. This study used cotinine level, a biomarker for nicotine, to investigate the relationship between prenatal smoking and autism. The authors conducted a population‐based case–control study nested in a national cohort of all births in Finland from 1987 to 2005. Cases diagnosed with childhood autism (ICD‐10/9 code F84.0/299.0) through 2007 were identified using data from linked national registers. Each case was matched with a control on date of birth (±30 days), sex, and place of birth ( N  = 962 pairs). Maternal serum cotinine levels were prospectively measured in first‐ to early second‐trimester serum samples archived in a national biobank using a quantitative immunoassay. Data were analyzed using conditional logistic regression. Prenatal maternal levels of serum cotinine were not associated with the odds of autism, whether cotinine was classified continuously, by deciles, or using previously defined categories corresponding to probable maternal smoking status. After adjusting for maternal age, paternal age, previous births, and any history of parental psychiatric disorder, the odds ratio for categorical high versus low cotinine, using a 3‐level exposure variable, was 0.98 (95% CI = 0.76, 1.26; p  = 0.88). In conclusion, this national birth cohort‐based study does not provide evidence for an association between maternal cotinine, a biomarker of maternal smoking, and risk of autism. Lay Summary: This study explored whether prenatal exposure to tobacco smoke in mothers is related to the diagnosis of autism in their children, by measuring the levels of cotinine, a biomarker for tobacco exposure, in stored serum samples drawn from mothers during pregnancy. The levels of cotinine in the mothers of children diagnosed with autism were similar to those in the mothers of control children of similar age and gender distribution.